Guy Debord e vanguardas: combate à sociedade do espetáculo - Casale, Luis Gustavo (2012)
The practical and theoretical activity of Guy Debord is marked by a strategy of refusal and combat which he called spectacle. He made his life trajectory an incessant war against the society of his time, in which understood the advent of commodity occupying all aspects of life, human and social, and consequently making it the totalizing domain of quantitative, reducing it to a mere game of appearances. Thus, this dissertation seeks to understand the nature of Debord s theoretical-practice activity, in the avant-garde groups that he directed, through themes that permeated this groups activities and also his writings and films, deliberately chosen as a strategic means to attack and refute the illusions of the spectacular-mercantile-society. At the end of the dissertation is noted that the avant-garde conception and theory in Debord has the same meanings, both are temporary, they should be used as a practical-critique of the present time, in the opportune moment. It was observed also by analyzing the concept of separation that the commodity fetish and reification reach the paroxysm in the society of the spectacle, historic stage of capital reproduction in which social relations are mediated by images